PROBLEMATIKA PEMBELAJARAN FIKIH MATERI MAWARIS PADA PESERTA DIDIK MADRASAH ALIYAH PESANTREN PEMBANGUNAN MUHAMMADIYAH TANA TORAJA - Yahya Santoso; Andi Achruh; Muhammad Iqbal; Muhammad Rusmin B.; Besse Ruhaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the challenges of teaching and learning Fiqh on Mawaris (Islamic inheritance law) material for students at Madrasah Aliyah Pesantren Pembangunan Muhammadiyah Tana Toraja. The purposes of this study are to describe the Fiqh learning process on Mawaris material, identify the challenges encountered, and analyze the contributing factors. This study employed a descriptive qualitative approach with a phenomenological orientation. Data were gathered from the madrasah principal, the Fiqh teacher, and twelfth-grade science students (XII-IPA) through observation, structured interviews, and documentation. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing, with data trustworthiness verified through triangulation. The results indicate that the Fiqh learning process on Mawaris material does not run optimally. The teacher has not developed a specific teaching module, the classroom instruction is still heavily dominated by the lecture method with limited media, and the evaluation system is not yet systematic. The emerging challenges include limited learning resources, a lack of variety in teaching methods, minimal utilization of learning media, and unstructured evaluations. The root causes consist of internal factors, such as low student motivation and disparities in students' mathematical calculation skills, as well as external factors, including limited time allocation, insufficient learning resources, and sub-optimal utilization of learning media. The implications of this study emphasize the urgent need for an integrated improvement in Fiqh instruction on Mawaris material across the planning, implementation, and evaluation phases.